SEX RATIO IN RATS AS A RESULT OF BEE POLLEN TREATMENT - Dosom, Kresensia Cyntia; Laksmi, Desak Nyoman Dewi Indira; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana; Vol. 15 No. 2 April 2023DO - 10.24843/bulvet.2023.v15.i02.p13, 2023)
The purpose of this study was to see how effective bee pollen is at determining sex in rats. This was an experimental study with three treatments and control group that used a completely randomized design. There was no bee pollen in control group. Then in P1, only female rats were given bee pollen (18mg), in P2 only male rats (22mg), and in P3 both male and female rats were given the same dose of bee pollen. Male and female rats were mated after receiving bee pollen for 49 days, and the sex ratio of the newborn rats was calculated after 21 days of gestation. ANOVA was used to analyze th data before proceeding with Duncan’s test. The findings of this study revealed that bee pollen could increase the proportion of male rats. This is because giving bee pollen to male rats allows more Y-chromosome spermatozoa to be produced and survive in this condition in the female reproductive tract. Andosperms benefit from this condition because they can move faster and more agilely than gynosperma. More male offspring are produced because the Y sperm (andosperm) or male sperm first reaches the egg and fertilizes it. Giving male and female rats bee pollen at the same time can increase the sex ratio of male rat pups.